Clinical and ultrasound features of non-specific aorto-arteriitis and aortic arch branch syndrome - O. A. Sivakova; N. M. Chikhladze; T. V. Balakhonova; V. I. Fedorova; I. E. Chazova (Кардиоваскулярная терапия и профилактика)
Aim. With duplex scanning method, to compare clinical symptoms of non-specific aorto-arteriitis (NAA) to aortic arch pathology registered. Material and methods. In total, 32 women with NAA were examined. Twenty-four patients underwent duplex scanning of aortic arch branches, carotid intima-media thickness measurement (high-definition ultrasound method; Vivid 7 device, GE, USA). All participants underwent clinical and neurological examination, with inflammation activity assessment. Results. Isolated pathology of aortic arch branches (Type I NAA) was observed in 6 (25%) out of 24 patients; Type III NAA (pathology of aortic arch branches, thoraco-abdominal aorta, and its visceral branches) - in 16 (66,7%); Type IV NAA (pulmonary artery pathology, regardless of any other lesion location) - in 2 (8,3%). Arterial hypertension (AH) was diagnosed in 18 (75%) out of 24 participants. In Type I NAA, AH clinical course was milder than in Type III and IV NAA. Functional neurological and emotional-affective disturbances were typical for NAA. Common carotid artery pathology was registered in 19 (79,2%) patients, and cerebral blood flow pathology - in 2 (8,3%) out of 24 participants. Conclusion. In NAA patients, brachiocephalic artery and common carotid artery pathology prevalence is relatively high. At the same time, strokes and transient ischemic attacks are rare.